FOREST DEGRADATION ASSESSMENT IN KALIMANTAN TROPICAL RAIN FOREST (KTRF) USING PHENOLOGICAL AND GEOMETRICAL SHAPE ANALYSIS - Darmawan, Mulyanto (Badan Informasi Geospasial in Partnership with MAPIN, 2010)
Kalimantan tropical rain forest (KTRF), for many years, has been subject for timber extraction, agriculture and plantation expansion, as well as settlement. Although it has experiencing ever land clearing, forest degradation both in spatial and temporal are poorly studied. Many researchersâ works in the forest field had considered that forest degradation is similar to deforestation. They defined a simple definition of deforestation as âconversion of forestâ. When such definition applied, it would create large area of forest degradation. In this study phenological analysis were applied to scale up the understanding of forest degradation in KTRF. In the initial stage, phenological analysis was evaluated using NDVI SPOT Vegetation 10 days composite. Secondly, K-mean classification and Knowledge Base Expert System (KBSE) method were applied to nine phenological metrics (Onset, End, Max, Min, AMP, RtUp, RtDn, and DUR, TIN) to calculate proportion of forest (Pof) and connectivity of forest with other non forest (Cof). Finally, the Geometrical shapes of forest were evaluated to understand forest degradation in Kalimantan forest. Result found that about 46% of Kalimantan forest has been threatened or experience with forest clearance which correspond to plantation and agriculture crops for 26,76% and of 19,24% was patch forest. While the other of 53% was represent natural forest. Of the 53% of the natural forest actually 55% was corresponding to transitional forest, perforated and edge forest at about 8%, 9% and 37% respectively. The critical point found in the phenological analysis mainly to determine the starting point of growing season (Onset) and the end of greenness (End).Keyword: tropical rain forest, deforestation, degradation, phenology analysis, geometrical shapeABSTRAKHutan hujan tropis Kalimantan (KTRF), selama bertahun-tahun, menjadi sumber pengambilan kayu, perluasan pertanian dan perkebunan, termasuk permukiman. Meskipun hutan ini mempunyai sejarah panjang pembukaan lahan (land clearing), informasi tentang degradasi hutan baik secara spasial maupun dan multi waktu sulit didapat. Banyak peneliti di sektor kehutanan menyederhanakan bahwa âdegradasi hutanâ adalah âdeforestasi hutanâ. Mereka menetapkan definisi sederhana deforestasi sebagai